(untitled) (Proceedings of the European Wave and Tidal Energy Conference, 2025)
the Open Sea Test Sites, which is called National Marine Test Site in China, plays an irreplaceable role in promoting the development and utilization of marine renewable energy. It provides R&D entities with complete, open, and shared test conditions, enhances the maturity of marine energy converters through field testing and evaluation, reduces R&D costs, and facilitates the development of green, safe, and pollution-free marine renewable energy. China has initiated the construction and operation of national marine test sites. In accordance with the layout of "North, East, South, shallow seas + deep seas", the Ministry of Natural Resources is systematically advancing the construction of national marine test sites. Currently, four national marine test site areas have been planned, namely Weihai, Zhoushan, Zhuhai and Shenhai. This paper introduces the functional positioning and construction progress of the four test sites in Weihai, Zhoushan, Zhuhai and Shenhai, and analyzes the core functions of each site area. On this basis, combined with the field testing requirements of tidal current and wave energy converters in China, the field testing and evaluation methods that have been carried out field testing work for tidal current and wave energy converters are introduced. The field testing systems developed for power characteristics and power quality characteristics are presented. Using the established field testing methods and the developed field testing systems, the field testing work were conducted on tidal current energy converters and wave energy converters. This paper aiming to provide references for technical exchanges and cooperation among international peers.